PELATIHAN DAN PENDAMPINGAN KEPADA PELAKU UMKM OLEH TAX CENTER UNIVERSITAS METHODIST INDONESIA - Thomas Sumarsan Goh; Dimita H. P. Purba; Rintan Saragih; Mulatua P. Silalahi; Yosephine N. Sembiring; Ivo M. Silitonga; Duma R. Situmorang; Arison Nainggolan; Rahel Junita; Tri Darma Sipayung; Farida Sagala; Putri J. Sitorus (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
The UMI tax center cooperates with the Regional Office of DJP Sumbagut 1 to assist MSME actors in improving and developing their products through appropriate marketing, namely digital marketing, recording transactions clearly, completely, and correctly, and in the future, MSME actors can make tax payments. As a result of this assistance, a win-win solution is created for the three parties; namely, MSME actors can gain knowledge and skills to increase sales and record transactions that are useful for decision making. The North Sumatra Regional Tax Office I can increase tax compliance. At the UMI Tax Center party, students have knowledge that directly handles tax cases at the time of tax reporting.